Analyses of the genetic diversity and population structures of Histoplasma capsulatum clinical isolates from Mexico, Guatemala, Colombia and Argentina, using a randomly amplified polymorphic DNA-PCR assay (2019)
ABSTRACT: We studied the genetic diversity and the population structure of human isolates of Histoplasma capsulatum, the causative agent of histoplasmosis, using a randomly amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) assay to identify associations with the geographic distribution of isolates from Mexico, Guatemala, Colombia and Argentina. The RAPD-PCR pattern analyses revealed the genetic diversity by estimating the percentage of polymorphic loci, effective number of alleles, Shannon’s index and heterozygosity. Population structure was identified by the index of association (IA) test. Thirty-seven isolates were studied and clustered into three groups by the unweighted pair-group method with arithmetic mean (UPGMA). Group I contained five subgroups based on geographic origin. The consistency of the UPGMA dendrogram was estimated by the cophenetic correlation coefficient (CCCr = 0.94, P = 0.001). Isolates from Mexico and Colombia presented higher genetic diversity than isolates from Argentina. Isolates from Guatemala grouped together with the reference strains from the United States of America and Panama. The IA values suggest the presence of a clonal population structure in the Argentinian H. capsulatum isolates and also validate the presence of recombining populations in the Colombian and Mexican isolates. These data contribute to the knowledge on the molecular epidemiology of histoplasmosis in Latin America.